As transformações socioespaciais da cidade de Tiradentes (MG) em função da emergência do turismo: um olhar possível para as décadas de 1970 a 1990 - Everton Rodrigues da Silva (2017)
This thesis` motivation is getting to know the social and cultural transformations that occurred in the city of Tiradentes (MG - Brazil), starting from the emergence of tourism, emphasizing its historical center. The aim is to also understand how the social subjects find their place in this dynamic. The chronological cut runs from the 1970s to the 1990s. This work is structured as follows: PART 1 - Building my outlook:approaching myself to Tiradentes (MG), divided into chapters 1 and 2, presents the general aspects of the past and the present of Tiradentes based on the academic and non-academic discourses produced about the city. Chapter 3, which focuses on Henri Lefebvre's space production concept and its developments, and Chapter 4, which brings complementary reflections on notions of identity, social change, andculture, compose PART 2 - Building my outlook: Theoretical Inspirations. Such theoretical inspirations should be understood as devices to stimulate the search for an individual outlook. PART 3 - Announcing ways of thinking and acting - addresses the place in the world that it is intended to be occupied as a researcher and presents the preliminary objectives of the research. PART 4 - Mixing myself into the research field - is a record of some experiences of the tiradentino everyday, the invention ofthe field of research and the processes of transformation observed. PART 5 - Light and Darkness ... establishes a (brief) look in retrospect, marking important passages throughout the doctorate, describing notes and gaps. The city of Tiradentes was apprehended as a cultural device, that is, as a space of multiple circuits (information), in which people, ideas, images, goods, etc. pass through. These circuits are amplified by information (moving through contact experiences) from local, regional,national and international places, where the singularity of the urban comes from its multiplicity of identity references. Engaging in the project of knowing the metamorphoses of Tiradentes is, therefore, to describe the historical processes of a cultural invention of city dwellers - or of cultural production /miscegenation/ hybridism. Therefore, attention was drawn to the interactions between individuals and the meanings created in these relationships. This purpose requires the knowledge to beelaborated from an ethnographic perspective inspired in this work, in the formulations of Eduardo Viveiros de Castro, Graça Índias Cordeiro, José Cantor Guilherme Magnani, Mariza Peirano, Michel Agier, Roy Wagner e Urpi Montoya Uriarte. In this way, the objective of the research was to describe the changes that took place in the tiradentino space, from the perspective of city dwellers, which implies direct observation (participant and non-participant), informal conversations, interviews andlife history records. The outlook of the outsiders who settled in the city in the 1970s and 1980s and who were involved in local transformational experiences was prioritized. The dialogues presented address, directly or indirectly, important problems posed by natives and outsiders: the reflection on the self-esteem of tiradentinos; the relevance of community mobilization; the action of relevant personalities in the construction of the city; the relation of the tiradentino with itsterritory; the reaction to the tourist festivals; the multiple identities in conviviality; the tensions and powers generated by the meeting of locals and outsiders; the relationship between memory and territory etc.